A Pathogenic Role for Splenic B1 Cells in SIV Disease Progression in Rhesus Macaques - Enyindah-Asonye, Gospel; Nwankwo, Anthony; Hogge, Christopher; Rahman, Mohammad Arif; Helmold Hait, Sabrina; Hunegnaw, Ruth; Ko, Eun-Ju; Hoang, Tanya; Venzon, David J.; Robert-Guroff, Marjorie (Frontiers in Immunology, 2019)
B1 cells spontaneously produce protective natural antibodies which provide the first line of defense against a variety of pathogens. Although these natural antibodies share similar autoreactive features with several HIV-1 broadly neutralizing antibodies, the role of B1 cells in HIV/SIV disease progression is unknown. We report the presence of human-like B1 cells in rhesus macaques. During chronic SIV infection, we found that the frequency of splenic CD11b+ B1 cells positively correlated with plasma SIV viral load and exhausted T cells. Mechanistically, we discovered that splenic CD11b+ B1 cells express PD-L2 and IL-10, and were able to induce PD-1 upregulation on CD4+ T cells in vitro. These findings suggest that splenic CD11b+ B1 cells may contribute to the regulation of SIV plasma viral load by enhancing T cell exhaustion. Therefore, understanding the mechanisms that govern their function in rhesus macaques may lead to novel therapeutic strategies for impeding HIV/SIV disease progression.